Effect of ospemifene on vaginal microbiome in postmenopausal women with vulvovaginal atrophy. Issue 4 (22nd April 2023) - Alvisi, Stefania; Ceccarani, Camilla; Foschi, Claudio; Baldassarre, Maurizio; Lami, Alessandra; Severgnini, Marco; Camboni, Tania; Consolandi, Clarissa; Seracchioli, Renato; Meriggiola, Maria Cristina
Abstract : This study analyzed the vaginal microbiome profiles in postmenopausal women with and without vulvovaginal atrophy (VVA) and assessed the effect of ospemifene and systemic hormone treatment on the vaginal microbiome of women with VVA. Women with VVA were characterized by a signifi cant reduction of Lactobacillus and a significant increase of bacterial diversity compared to women without VVA; both treatments improved vaginal microbiota, and ospemifene reduced potential harmful bacteria such as Staphylococcus and Clostridium. Abstract: Objectives: This study aimed (i) to compare the vaginal microbiome profiles of women suffering from vulvovaginal atrophy with that of healthy postmenopausal women and to (ii) assess the effect of ospemifene and systemic hormone treatment on the composition of the vaginal microbiome. Methods: Sixty-seven postmenopausal women attending the Gynecology Clinic of Azienda Ospedaliero-Universitaria of Bologna (Italy) were enrolled. Of them, 39 received a diagnosis of atrophy and 28 were considered healthy controls. In the group of atrophic women, 20 were prescribed ospemifene and 19 received hormone treatment. The vaginal health index was calculated, and a vaginal swab was collected for the assessment of vaginal maturation index and the analysis of vaginal microbiome through 16S rRNA gene sequencing. Clinical/microbiological analyses were repeated after 3 months of treatment. Results: The vaginal microbiome of atrophic women was characterized by a significant reduction of Lactobacillus ( P = 0.002) and an increase of Streptococcus ( P = 0.008) and Sneathia ( P = 0.02). A positive correlation between vaginal health index/vaginal maturation index and Lactobacillus abundance was found ( P = 0.002 and P = 0.035, respectively). Both therapeutic approaches effectively improved vaginal indices. Systemic hormone treatment induced changes in minority bacterial groups of the vaginal microbiome, whereas ospemifene was able to eliminate specific bacterial taxa, such as Staphylococcus ( P = 0.04) and Clostridium ( P = 0.01). Both treatments induced a trend in the increase of bifidobacteria. Conclusions: The vaginal microbiome of atrophic women differs significantly from that of healthy postmenopausal women. Ospemifene may lead to a condition of vaginal health, likely characterized by the reduction of "potentially harmful" bacteria.